Exchange rate pass-through and inflation dynamics in Tunisia: A Markov-switching approach - Rim Khemiri; Mohamed Sami Ben Ali (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
This paper studies the effect of exchange rate pass-through on inflation in Tunisia for the period 2001 to 2009. The objective is to track inflation regimes for the Tunisian economy and to forecast its determinants. Using a Markov-switching approach, the authors identified two main regimes for inflation in Tunisia during this period: a low and stable inflation regime associated with a low pass-through level and a high inflation regime associated with a high pass-through level. To highlight the mechanisms underlying shifts in inflation regimes, the authors used a time-varying probabilities approach and identified a set of variables to assess their effects on inflation in Tunisia. The results show that the price level decreases in response to an increase in interest rates. Along with this, the empirical results provide strong evidence that the industrial production index has a negative and significant effect, as it increases the probability to stay in an inflationary regime and remain at a high pass-through level. The results also show robust support for the hypothesis that the imports increase the probability to stay in a high-inflation regime and maintain a high pass-through level. However, exports increase the probability of staying in a low-inflation regime and maintaining a low pass-through level.
Keywords: G15; F3; F4; 330; Pass-through; Inflation; Markov-switching; Economic Fundamentals